Trinity and Mission: The Body of the Sending: Suggestions Inspired by Levinas - Duque, João Manuel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
In an attempt to understand the Trinitarian foundation of the mission, a reinterpretation of the Trinitarian theology itself is proposed, based on the categories of responsivity and responsibility, understanding the Trinitarian processions as processes of sending or calling towards responsibility. Using the category of mediation, an interpretation of the Trinitarian dynamics as historical dynamics is also suggested, in the ecclesial body or even in the history of human daily life. To be called to the responsibility for the other, in a situated response is the embodiment of the Trinitarian relations themselves.
Keywords: Trinidad; mission; responsibility; vocation; identity